Factors Associated with Loss to Follow-Up (LtFU) Among People Living with HIV/AIDS: A Scoping Review - Widyahandayani, Dian; Sriatmi, Ayun; Suryoputro, Antono (Jurnal Ners, 2026)
HIV/AIDS remains a global health problem with an increasing number of cases, including in Indonesia. One major challenge in HIV management is Loss to Follow-Up (LtFU), defined as patients missing clinical visits for more than 90 days, which threatens antiretroviral (ARV) treatment success by increasing the risk of drug resistance, treatment failure, morbidity, and mortality. This scoping review aimed to identify determinants associated with LtFU among people living with HIV/AIDS. Literature searches were conducted in national and international databases for studies published between 2021-2025, yielding 38 eligible studies. Result of thematic analysis finding indicate that LTFU is influenced by multidimensional factors, including demographic (young age, male, unmarried/divorced), socio-economic and geographic (rural residence, long distance to healthcare facilities, low education, loss of income), clinical and biomedical (low CD4 count, high viral load, advanced HIV stage, malnutrition, TB coinfection), treatment and adherence (low ART adherence, no regimen change, early ART initiation, absence of prophylactic therapy), and psychosocial and health system factors (stigma, non-disclosure, perceived wellness, side effects, limited provider support, weak tracing systems). In conclusion, addressing LTFU requires multidimensional interventions integrating clinical, educational, social, and system-level strategies to enhance patient retention in HIV care.